The changing demography of the cystic fibrosis population: forecasting future numbers of adults in the UK - Keogh, Ruth H. (Sci Rep, 2020)
Improvements in management of cystic fibrosis (CF) through specialist centres in the UK have been associated with a step-change in life expectancy. With increasing numbers of adult patients there is a need to review health care provision to ensure it is sufficient to meet future needs. We used UK CF Registry data to project the number of patients aged 16–17 and 18 and older  up to 2030, and numbers therefore requiring specialist adult CF care. Survival modelling was used to estimate age-specific mortality rates. New-diagnosis rates were estimated using diagnoses observed in the Registry and national population figures. Uncertainty in projections was captured through 95% prediction intervals (PI). The number of adults (aged 18 and older) is expected to increase by 28% from 6,225 in 2017 to 7,988 in 2030 (95% PI 7,803–8,169), assuming current mortality rates. If mortality rates improve at the rate seen over recent years, the projected number increases to 8,579 (95% PI 8,386–8,764). The age distribution is also expected to change, with 36% of CF adults being over 40 in 2030, versus 21% in 2017. There is an urgent requirement to review adult CF health care provision, due to both increasing numbers and the changing care needs of an older population.